2020
DOI: 10.1038/s41598-020-70410-6
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and white matter connections of the fusiform gyrus

Abstract: the fusiform gyrus is understood to be involved in the processing of high-order visual information, particularly related to faces, bodies, and stimuli characterized by high spatial frequencies. A detailed understanding of the exact location and nature of associated white-tracts could significantly improve post-operative morbidity related to declining capacity. through generalized q-sampling imaging (GQi) validated by gross dissection as a direct anatomical method of identifying white matter tracts, we have cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…The thalamic peak coordinates of the response inhibition paradigm seemed to overlap with our PFC_thalamus that further support our study. Our investigation complemented the findings of thalamus in heroin‐related cognitive literature by showing negative correlation between TMT‐A scores and thalamic RSFC with several regions, including ITG (involved in visual comprehensions), fusiform (involved in the processing of visual information) and precuneus (involved in environmental monitoring and awareness) (Cavanna & Trimble, 2006; Lin et al, 2020; Palejwala et al, 2020). We found the involvement in information processing of PFC_thalamus‐centered circuits, a potential neuroimaging biomarker of cognitive impairment in acute abstinent HU.…”
Section: Discussionsupporting
confidence: 82%
“…The thalamic peak coordinates of the response inhibition paradigm seemed to overlap with our PFC_thalamus that further support our study. Our investigation complemented the findings of thalamus in heroin‐related cognitive literature by showing negative correlation between TMT‐A scores and thalamic RSFC with several regions, including ITG (involved in visual comprehensions), fusiform (involved in the processing of visual information) and precuneus (involved in environmental monitoring and awareness) (Cavanna & Trimble, 2006; Lin et al, 2020; Palejwala et al, 2020). We found the involvement in information processing of PFC_thalamus‐centered circuits, a potential neuroimaging biomarker of cognitive impairment in acute abstinent HU.…”
Section: Discussionsupporting
confidence: 82%
“…On the implication of our results on the role of imagery in insight, we also examined the effects of high and low problem imageability on the insightful constraint relaxation of CRR riddles and found that high imagery of the problem situations for CRR puzzles evoked more activation in the visuospatial areas in the fusiform, lingual, and parahippocampal gyri (Howard et al, 1998; Nemmi, Boccia, Piccardi, Galati, & Guariglia, 2013; Palejwala et al, 2020; Roberts et al, 2013; Stern et al, 1996; Zhang et al, 2016; Zhang, Liu, & Zhang, 2014) than did the low ones, which is in line with a previous study of the effects of imagery on logic reasoning (Knauff et al, 2003). However, no superthreshold pMTG/AG activation was observed in the contrasts between the highly and poorly imageable CRR items (Although there was a left inferior parietal lobule [BA 40] activation adjacent to pMTG/AG observed in that contrast, the cluster size was relatively small [75 voxels].…”
Section: Discussionmentioning
confidence: 82%
“…Our finding of a reduced interaction between specific subareas of the occipital lobe and the cerebellar hemisphere supports the evidence that the remote influence between structurally segregated regions with distinct functional profiles may exist even in the absence of direct anatomical projections, through indirect polysynaptic pathways of connection ( 41 , 90 ). Although the precise function of the OFusG has not been fully revealed yet, it has been implicated in high-level visual processing, such as categorical recognition of visual stimuli ( 91 , 92 ), and in those processes characterized by high recurrence of perceptual ambiguity ( 93 ). It is noteworthy that the PD motor performance is prone to deterioration with increasing ambiguous visual stimuli.…”
Section: Discussionmentioning
confidence: 99%